2020
DOI: 10.3389/fmicb.2019.02962
|View full text |Cite|
|
Sign up to set email alerts
|

Dual NDP52 Function in Persistent CSFV Infection

Abstract: Viruses have evolved many mechanisms to escape host antiviral responses. Previously, we found that classical swine fever virus (CSFV) infection induces autophagy using the autophagosome as a self-replication site, thereby evading the host immune response and promoting long-term infection. However, the underlying mechanisms used by CSFV to enter autophagosomes and the mechanism by which autophagy promotes viral replication remain unclear. We found that CSFV infection inhibited autophagy receptor nuclear dot pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 54 publications
0
12
0
Order By: Relevance
“…Our results show that inhibiting NDP52 boosts interferon and release and promotes NF-κB pathway activation. In summary, we found that NDP52 inhibition not only reduces CSFV binding and entry into autophagic vesicles, but also inhibits CSFV replication by active NF-κB antiviral immune pathways [100] (Figure 4). Our data reveal a novel mechanism by which NDP52, an autophagy receptor, mediates CSFV infection, and provides new avenues for the development of antiviral strategies.…”
Section: The Role and Mechanism Of Ndp52 In Viral Infectionsmentioning
confidence: 76%
“…Our results show that inhibiting NDP52 boosts interferon and release and promotes NF-κB pathway activation. In summary, we found that NDP52 inhibition not only reduces CSFV binding and entry into autophagic vesicles, but also inhibits CSFV replication by active NF-κB antiviral immune pathways [100] (Figure 4). Our data reveal a novel mechanism by which NDP52, an autophagy receptor, mediates CSFV infection, and provides new avenues for the development of antiviral strategies.…”
Section: The Role and Mechanism Of Ndp52 In Viral Infectionsmentioning
confidence: 76%
“…(7) Proteins related to MAPK signaling pathways, such as TRAF5 [80] and MEK2 [81,82], could promote CSFV replication. (8) Some proteins involved in autophagy or apoptosis, such as BECN1, LC3 [83], NDP52 [84], and FHC [85], also could regulate CSFV replication. (9) Other proteins were also reported to be involved in the CSFV replication, such as FKBP8 [86], Jiv90 [87], HSP70 [88], HO-1 [89], and AIF1 [90].…”
Section: Host Proteins Whose Function Defect Exert Anti-csfv Effectsmentioning
confidence: 99%
“…The classical swine fever virus (CSFV) was recently reported to cause down-regulation of CALCOCO2/NDP52 as well as decreased ubiquitination and SUMOylation (small ubiquitin-like modifier) of the receptor or its binding partners in a Parkin dependent manner [ 25 ]. Parkin was upregulated and Parkin, or Parkin associated proteins, were ubiquitinated as a response to CSFV infection.…”
Section: Introductionmentioning
confidence: 99%
“…Parkin was upregulated and Parkin, or Parkin associated proteins, were ubiquitinated as a response to CSFV infection. CALCOCO2/NDP52 silencing decreased CSFV replication measured by viral titers, RNA copy numbers and reduction of viral protein N pro , indicating a positive role for CALCOCO2/NDP52 in CSFV replication [ 25 ]. CSFV structural protein E2 was observed colocalizing with CALCOCO2/NDP52 in PK-15 cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation